Prevalence and seasonal distribution of haemosporidian parasites in pigeons of mymensingh and rangpur districts, bangladesh - Md . Tanvick Zahan; Md. Shahadat Hossain; Anita Rani Dey; Md. Shahiduzzaman; Mohammad Zahangir Alam (Eurasian Journal of Veterinary Sciences)
Aim: The present epidemiological investigation was carried out to investigate the status of pigeon haemosporidian parasites in two districts (Mymensingh and Rangpur), Bangladesh. Materials and Methods: In total, 300 blood samples of pigeons were examined from January to November, 2016. Blood samples were collected from wing vein and thin smears were prepared from them. All smears were stained with Giemsa stain and examined under microscope. Results: The overall prevalence of haemosporidian parasites was 28% (84 /300) in pigeons. Of those, 22.3% (67/300) of birds were infected with Haemoproteus spp., 5.7% with Plasmodium spp. (17/300) and 2.7% with both genera (8/300). The prevalence rate was insignificantly (p = 0.050) higher in Mymensingh (34.7%) than in Rangpur (24.2%). Male were more susceptible (30.8%) than female (25.3%). Adults (29.5%) were more prone to infectione than young (19.6 %). The prevalence was significantly (p = 0.000) higher in the rainy season (56.1%) followed by summer (33.8%) and winter (10.0%).<p< Conclusion: From this study, it was ascertained that avian malaria in pigeons was prevalent in Bangladesh. Therefore, further investigations with a larger sample size and molecular characterization of avian malaria species in pigeons of Bangladesh is warranted.